Agricultural land use in Vietnam in the context of urbanization: status and policy implications - Huyen Phan Thi Thanh; Giang Pham Quy (Environmental & Socio-economic Studies, 2024)
This article generalizes the urbanization process and its impact on agricultural land use in Vietnam. The high rate of urbanization has led to a great demand for purchasing agricultural products, especially high-quality ones, and as a result, this affects agricultural development. On one hand, it offers new chances to expand the domestic market and to encourage exports. On the other hand, the conversion of agricultural land into non-agricultural land under accelerated urbanization leads to a large area of arable land being abandoned or polluted, consequently affecting food security and sustainable development. Therefore, to meet the people’s food needs in the context of urbanization, it is necessary to have proper solutions to improve the efficiency of agricultural land use, such as: implementing land laws aimed at developing agricultural production in the direction of large-scale, concentrated commodities; executing land-use planning, performing agricultural production planning towards specialized cultivation with a stable term to ensure profitable investment; boosting the restructuring of the agricultural sector; developing collective and cooperative economics in agriculture; having policies to support, forecast, and search for markets for consumption and the processing of agricultural products; creating a transparent land-use rights market.